EPR investigation of pure and Co-doped ZnO oriented nanocrystals. (14th December 2016) - Savoyant, A; Alnoor, H; Bertaina, S; Nur, O; Willander, M
Abstract: Pure and cobalt-doped zinc oxide aligned nanorods have been grown by the low-temperature (90 °C) aqueous chemical method on amorphous ZnO seed layer, deposited on a sapphire substrate. High crystallinity of these objects is demonstrated by the electron paramagnetic resonance investigation at liquid helium temperature. The successful incorporation of Co 2+ ions in substitution of Zn 2+ ones in the ZnO matrix has also been confirmed. A drastic reduction of intrinsic ZnO nanorods core defects is observed in the Co-doped samples, which enhances the structural quality of the NRs. The quantification of substitutional Co 2+ ions in the ZnO matrix is achieved by comparison with a reference sample. The findings in this study indicate the potential of using the low-temperature aqueous chemical approach for synthesizing material for spintronics applications.